KETERAMPILANPEMBUATAN MEDIA PEMBUDIDAYAAN BELUT BAGI ANAK TUNARUNGU - Joni - Wandri (Jurnal Penelitian Pendidikan Khusus, 2013)
This research background by deaf children in learning class VIII SMPLB breeding eels in particular exerting skill is necessary in children with hearing impairment due to give to the child's location close to the market piladang where eels are a marketable commodity and begin training in the field of entrepreneurship aims eventually to be children more independent in performing live. During this new kid knows how to capture that are naturally disawah / swamp fish trap use, children can not do farming skills mainly manufacture medium to cultivate eel. The use of methods of demonstration in the manufacture of eel cultivation media provide an immediate impact in engaging students and accompanied by providing exercises to what students are learning to acquire a particular skill. This study aims to determine how teacher training media creation breeding eels in children with hearing impairment. Methodology of this study is action research (classroom action research) is done in the form of collaboration. These actions were taken to two children who are the subject of research that deaf children in the eighth grade SMPLB SLB Image Nation. The results showed in the first cycle held seven meetings and the second cycle of twelve meetings in the learning process starts from the child to know the tools and materials used, as well as the usefulness of each ingredient in the manufacture of tools and eel cultivation media and how to choose and determine good material in the manufacture of eel cultivation media. Based on the average value obtained by the students in the given action AG before getting a value of 20% in the introduction of tools and materials in the manufacture of media while cultivating eel obtain the value of 13% at the end of the first cycle and 73% scored in the second cycle gain value of 75%. Students are given the SC prior to the action to get a value of 26% in the introduction of tools and materials in the manufacture of media while cultivating eels obtained a value of 25%. the end of the cycle I get the value of 78% and in the second cycle could be 88% scored. Based on these results it can be concluded that the method of demonstration can be used to train the manufacture of eel cultivation media for deaf children. Advised on schools, teachers and researchers can use to further demonstration method in teaching others exerting skills in children with hearing impairment.